Supersonic propagation of lattice energy by phasons in fresnoite - M. E. Manley (Nature Portfolio, 2018)
Fresnoite has an incommensurate structure that can be described as a nonlinear soliton lattice. Manley et al. show that the additional phason degrees of freedom associated with the solitonic structure can travel faster than more conventional phonon excitations, enabling supersonic energy transport.